When given two choices, take both! Social impact assessment in social entrepreneurship - Muñoz, Pablo; Gamble, Edward (Entrepreneurship & Regional Development, 2024)
This paper examines how social entrepreneurs construct impact arguments as they begin to assess social impact. We examined the experiences of 68 social entrepreneurs in Chile and discovered that the construction of arguments for the purpose of thinking about and experiencing impact is different than the arguments constructed to establish dialogues around it. We explain this dual argument construction as arguments for worth and arguments for legitimacy. We expand scholarship on argumentation by clarifying social entrepreneurs’ efforts to pursue adherence facing competing demands and reinforcing their willingness and ability to engage with social impact assessment. We advance the understanding of social impact assessment in social entrepreneurship across three areas: tensions, accountability and performance and extend Nicholls’ general theory by explaining what precedes the discursive space where the assessment of social impact reconciles facticity and validity to establish materiality.
RRS checked